Effect of plant growth regulators on growth and quality of onion (Allium cepa L.) (International Journal of Food and Nutritional Sciences, 2022)
A field experiment was conducted at the instructional Farm, AKS University, Sherganj, Satna(M.P.) for season 2022-2023. To study the effect of plant growth regulators on growth andquality of onion (Allium cepa L.). The trial was laid down in randomized block design (RBD)with three replications and twelve treatments viz. T0- Control, T1- NAA 100 ppm, T2- NAA150 ppm, T3 - NAA 200 ppm, T4 - NAA 300 ppm, T5- Ethrel 100 ppm, T6- Ethrel 200 ppm,T7 - Ethrel 300 ppm, T8 - GA3 100 ppm, T9 - GA3 150 ppm, T10 - GA3 200 ppm and T11 –GA3 300 ppm. Study results revealed that, the application of T11 (GA3 300 ppm) registeredhighest plant height, leaves/plant, neck diameter, bolting percentage, Length of bulb,Diameter of bulb and Bulb yield (t/ha). Maximum plant height (44.57 cm at 90 DAT),Number of leaves per plant (9.92 at 90 DAT), neck diameter (2.30 cm at 90 DAT) andbolting percentage (1.55 % at 90 DAT), Length of bulb (7.67 cm) Diameter of bulb (6.44cm) and bulb and Bulb yield (t/ha) (44.71 t/ha).